A Handbook of the Aramaic Scrolls from the Qumran Caves Manuscripts, Language, and Scribal Practices - Machiela, Daniel (Brill, 2022)
This book provides the first comprehensive treatment of the Aramaic Dead Sea Scrolls from the caves of Qumran. These nearly one hundred scrolls open a window onto a vibrant period of Jewish history for which we previously had few historical sources. Scholars and advanced students will find a general introduction to the corpus, detailed, richly-illustrated profiles of individual scrolls, and up-to-date studies of their Aramaic language and scribal practices. The goal of the book is to foster and support further study of these scrolls against the historical backdrop of early Judaism and ancient Mediterranean scribal cultures.